The Effect of Synectic Learning Model and Learning Interests on Creative Thinking Ability in Writing Free Poetry for Class V Students of SD Negeri 112320 Aek Kota Batu - Desi Susanty; Abdurahman Adisaputera; Anita Yus (BIRCU, 2020)
This study aims to determine: (1) To determine the differences in students' creative thinking skills in writing free poetry between students who are taught with the synectic learning model compared to the reciprocal learning model; (2) To determine the differences in students' creative thinking skills in writing free poetry between students who have high learning interest compared to low learning interest; and (3) to determine the interaction between learning models and interest in learning in influencing students' creative thinking abilities in writing free poetry. This research was conducted at SDN 112320 Aek Kota Batu. The research method used is a quantitative method with a 2x2 experimental design. Data collection techniques used questionnaires and tests. The data analysis technique in this study used the Two Way Anova test. The results showed that: (1) There is a significant difference in the average creative thinking ability of students who are taught with the synectic model compared with the average thinking ability of students taught with the reciprocal model (Fcount = 11.664 and sig. 0.001 < 0.05) ; (2) The average creative thinking ability of students who have high learning interest is higher than the average creative thinking ability of students who have low learning interest (Fcount = 12.165 and sig. 0.001 < 0.05); and (3) There is an interaction between learning models and interest in learning in influencing students' creative thinking abilities (Fcount = 7.054 and sig. 0.011 < 0.05).